2018
DOI: 10.3390/f9030150
|View full text |Cite
|
Sign up to set email alerts
|

Community Forestry for Livelihoods: Benefiting from Myanmar’s Mangroves

Abstract: Abstract:It is well known that in many rural communities in the developing world, forests, particularly those under community management, are important for people's livelihoods. However, studies on the contribution of forests to the income of different households within a community are rare, including the poorest households and how non-members of the community forestry user group (CFUG) benefit from those resources. This paper compares livelihood strategies and the use of a mangrove CF by different community m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Community forestry schemes coupled with management plans for a sustainable use of resources arguably contribute more to conservation [65][66][67] and the provision of a holistic bundle of ES. Studies have even shown that community forests in Myanmar can also reduce disparities by contributing to the livelihoods of different subgroups within a community [68]. Inclusion of local people's perspectives is a major advantage and prerequisite for community forests.…”
Section: Outlook For Tanintharyi Regionmentioning
confidence: 99%
“…Community forestry schemes coupled with management plans for a sustainable use of resources arguably contribute more to conservation [65][66][67] and the provision of a holistic bundle of ES. Studies have even shown that community forests in Myanmar can also reduce disparities by contributing to the livelihoods of different subgroups within a community [68]. Inclusion of local people's perspectives is a major advantage and prerequisite for community forests.…”
Section: Outlook For Tanintharyi Regionmentioning
confidence: 99%
“…In addition, seasonal crops, fodder, fuelwood, and thetke (Cylindrical imperator) are the main forest products of plantation-type CFs in the dry zone [63]. Wood, non-timber forest products, mud crab (Scylla serrata), and nypa palm (Nypa fruticans) are also extracted from mangrove CFs in delta areas [64]. Although previous studies of forest dependency in the CFs of Myanmar have been conducted in different parts of the country, including the dry zone and delta areas (e.g., [63,64]), they have focused exclusively on forest dependency in terms of livelihood strategies [64] and participation in CF activities [63].…”
Section: Forest Dependencymentioning
confidence: 99%
“…Wood, non-timber forest products, mud crab (Scylla serrata), and nypa palm (Nypa fruticans) are also extracted from mangrove CFs in delta areas [64]. Although previous studies of forest dependency in the CFs of Myanmar have been conducted in different parts of the country, including the dry zone and delta areas (e.g., [63,64]), they have focused exclusively on forest dependency in terms of livelihood strategies [64] and participation in CF activities [63]. For example, Feurer et al [64] reported that CF members earned higher forest income from mangrove CFs than non-CF members.…”
Section: Forest Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Issues about livelihoods and poverty in affected areas are mentioned in the EU FLEGT Action Plan. e challenge to overcome this issue is to ensure that actions to deal with illegal logging, especially increasing law enforcement [39]. On the other hand, let the players of illegal logging influence without being touched by the law [40].…”
Section: Effect Of Vpamentioning
confidence: 99%